Online Shopping Intention and Behaviour of Young and Older Adults in Malaysia. A Theory of UTAUT2 - Ng, Weng Bu (2016)
Unified Theory of Acceptance and Use of Technology 2 (Venkatesh et al, 2012) is a relatively new theory and research conducteded was mostly in the context of developed economies. The purpose of this study is to complement existing literacture by the influencing factors of online shopping intention using UTAUT2 among shoppers in Malaysia. The effect of age on online shopping behaviour is also tested using two age groups: younger adults (below 40 years old) and older adults (above or equal to 40 years old). This study also examine consumers’ willingness to puchase online and online shopping beahviour. Quantitative methodology was employed, using multiple regression analysis to text the hypotheses. Convenient sampling was applied. Findings of the study indicate that Effort Expectancy, Social Influence, Facilitating Condition, Price Value and Habits have significant positive relationship towards consumers’s intention to shop online. Interestingly, Performance Expectancy and Hedonic Motivation do not have a significant relationship towards consumers’ online shopping intention. In fact, Habits and Price Value are the stronger predictors of consumers’ online shopping intention. When comparing younger and older adults, results show no evidence of significant differences between these two age groups. Recommendations are presented to assist service providers and marketers in Malaysia to understand online shopping behaviour and influencing factors of online shoping intention so as to formulate effective marketing strategies to promote online shopping. This study concludes with a discussion on research limitation and future research recommendations are also presented.